A gamificação como estratégia para a formação de leitores literários no ensino fundamental - Moreira, Cláudia dos Santos (2018)
This dissertation presents a research about the use of gamification as a strategy for the training of literary readers in elementary school, investigating the potentialities and limitations of the strategy when combined with the work with literature, also presents a pedagogical product, a requirement of the Professional Master in Language Teaching. The perception of the need to use new technologies and methodologies to contribute to the formation of readers in a public school context, with all the ills and challenges already known, is one of the justifications of this research, which considers literary reading as a means of transforming subjects and self-perception as a historical agent. To investigate the effectiveness of the strategy, in May 2017, a pedagogical intervention was carried out in a group of 8th grade students from a public school located in Alegrete, RS. The proposal provided the students with moments of reading and expansion of the repertoire of literary readings and the construction of gamified activities. As a theoretical basis of the research, authors such as Rildo Cosson, Ana Maria Machado, Regina Zilberman, Roger Chartier, Hans Robert Jauss, Teresa Colomer, were used to deal with concepts and specificities about reading, literature and literary literacy. About digital technologies, digital literacy and gamification, studies were based on Marcelo Busato, Vilson Leffa, Pierre Lévy, Prensky and Deterting. The methodology focused on bibliographic research and action research that consisted in the implementation of a sequence of activities that were analyzed and interpreted based on the theoretical assumptions studied. The study also involved reflection on the teaching of the researcher. The main results show that: (a) gamification is an efficient strategy in the training of literary readers because it can motivate students to read, developing the use of skills, skills, cooperation and collaboration; (b) it is desirable that teachers take ownership of digital literacy concepts to make use of technological resources such as gamification; (c) not all literary works have the same potential for suitability to gamification. The work demonstrates that gamification cannot be understood as a "magic solution" to solve the difficulties encountered in teaching literary reading, but rather as an active, possible and viable methodology to be implemented in Brazilian schools. In this sense, we believe that gamification needs to be broadly disseminated so that teachers know it and make good use of it, thus facilitating the process of teaching and learning, especially in the training of literary readers.